2012
DOI: 10.1128/jvi.06992-11
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Saimiri Antagonizes Nuclear Domain 10-Instituted Intrinsic Immunity via an ORF3-Mediated Selective Degradation of Cellular Protein Sp100

Abstract: In recent studies, the nuclear domain 10 (ND10) components PML, Sp100, human Daxx (hDaxx), and ATRX were identified to be cellular restriction factors that are able to inhibit the replication of several herpesviruses. The antiviral function of ND10, however, is antagonized by viral effector proteins by a variety of strategies, including degradation of PML or relocalization of ND10 proteins. In this study, we analyzed the interplay between infection with herpesvirus saimiri (HVS), the prototypic rhadinovirus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 46 publications
(54 reference statements)
3
48
0
Order By: Relevance
“…Human CMV (HCMV) and herpesvirus saimiri (HVS) target Sp100 for proteasomal degradation; depletion of Sp100 by RNA interference enhances HCMV replication and gene expression (83,112,113). Similar to our findings, Maul and coworkers previously demonstrated that Sp100 isoforms B, C, and HMG, but not Sp100A, suppressed HSV-1 immediate early gene expression and repressed the ICP0 promoter and that this was dependent on the SAND domain (114).…”
Section: Discussionsupporting
confidence: 76%
“…Human CMV (HCMV) and herpesvirus saimiri (HVS) target Sp100 for proteasomal degradation; depletion of Sp100 by RNA interference enhances HCMV replication and gene expression (83,112,113). Similar to our findings, Maul and coworkers previously demonstrated that Sp100 isoforms B, C, and HMG, but not Sp100A, suppressed HSV-1 immediate early gene expression and repressed the ICP0 promoter and that this was dependent on the SAND domain (114).…”
Section: Discussionsupporting
confidence: 76%
“…EpsteinBarr virus (EBV) disrupts ND10 and the ATRX-hDaxx complex through the actions of BZLF1 and BNRF1, respectively (8,72), and causes a dispersal of Sp100 and hDaxx from ND10 during lytic replication (73). Along the same lines, the murine gammaherpesvirus 68 tegument protein orf75c induces degradation of PML (74), while the related protein ORF3 of herpesvirus saimiri specifically degrades Sp100 but affects neither PML nor hDaxx (75). Although via different mechanisms and mediated by viral regulatory proteins that in most cases have little or no sequence similarity, all of these viruses appear to target the same group of cellular proteins to counteract the initial repression of viral gene expression and promote virus replication.…”
Section: Discussionmentioning
confidence: 95%
“…For KSHV, it has been shown that shortly after infection, PML-NB components localize to viral genomes and prereplication compartments (147). Interestingly, PML is SUMO-2 modified by LANA2, the latency-associated nuclear antigen 2.…”
Section: Nuclear Dna Virus Replication Centersmentioning
confidence: 99%
“…Thus, members of the gammaherpesvirus family, like Kaposi's sarcoma-associated herpesvirus (KSHV) (147), herpesvirus saimiri (HVS) (148), and Epstein-Barr virus (EBV) (152), express proteins with properties similar to HSV-1 ICP0. Furthermore, viral replication compartments develop in association with PML-NB remnants (147,148,152).…”
Section: Nuclear Dna Virus Replication Centersmentioning
confidence: 99%